Modeling dynamics of a building using a portal frame approach - Cheah, Yee Mun; Putra, Azma; Muhammad, Noryani; Dullah, Abd Rahman; Jenal, Ruztamreen (Praise Worthy Prize, 2017)
Building service equipment, such as ventilators, air conditioners, and cooling tower are structure-borne sources that are capable of injecting vibration input power to the building structure. The vibration waves propagate through the building elements and can result in audible low frequency noise. This paper proposes the development of an analytical model of the dynamics of a building using a two-dimensional portal frame structure consisting of beam and truss elements. The structural response due to an injected force from a structure-borne source is studied and is compared with a three-dimensional model from the Finite Element Method. It is shown that the vibration pattern from the two-dimensional result follows the pattern of that from the three-dimensional model for vertical vibration. The two-dimensional model can thus be used for a simple modelling to understand the behavior of the building vibration.